Current and future functional imaging techniques for post-traumatic stress disorder. Issue 42 (8th August 2019) - Prasad, Alisha; Chaichi, Ardalan; Kelley, D. Parker; Francis, Joseph; Gartia, Manas Ranjan
Abstract : Conventional methods of studying posttraumatic stress disorder (PTSD) have proven to be insufficient for diagnosis. We have reviewed clinical and preclinical imaging techniques as well as molecular, cellular, and behavioral indicators for PTSD. Abstract : Posttraumatic stress disorder (PTSD) is a trauma and stressor related psychiatric disorder associated with structural, metabolic, and molecular alternations in several brain regions including diverse cortical areas, neuroendocrine regions, the striatum, dopaminergic, adrenergic and serotonergic pathways, and the limbic system. We are in critical need of novel therapeutics and biomarkers for PTSD and a deep understanding of cutting edge imaging and spectroscopy methods is necessary for the development of promising new approaches to better diagnose and treat the disorder. According to the Diagnostic and Statistical Manual of Mental Disorders (DSM-V) criterion, all forms of traumatic stress-induced disorder are considered acute stress disorder for the first month following the stressor. Only after symptoms do not remit for one month can the disorder be deemed PTSD. It would be particularly useful to differentiate between acute stress disorder and PTSD during the one month waiting period so that more intensive treatments can be applied early on to patients with a high likelihood of developing PTSD. This would potentially enhance treatment outcomes and/or prevent the development of PTSD. Comprehension of the qualities and limitations of currently applied methods as well as the novel emerging techniques provide invaluable knowledge for fast paced development. Conventional methods of studying PTSD have proven to be insufficient for diagnosis, measurement of treatment efficacy, and monitoring disease progression. As the field currently stands, there is no diagnostic biomarker available for any psychiatric disease, PTSD included. Currently, emerging and available technologies are not utilized to their full capacity and in appropriate experimental designs for the most fruitful possible studies in this area. Therefore, there is an apparent need for improved methods in PTSD research. This review demonstrates the current state of the literature in PTSD, including molecular, cellular, and behavioral indicators, possible biomarkers and clinical and pre-clinical imaging techniques relevant to PTSD, and through this, elucidate the void of current practical imaging and spectroscopy methods that provide true biomarkers for the disorder and the significance of devising new techniques for future investigations. We are unlikely to develop a single biomarker for any psychiatric disorder however. As psychiatric disorders are incomparably complex compared to other medical diagnoses, its most likely that transcriptomic, metabolomic and structural and connectomic imaging data will have to be analyzed in concert in order to produce a dependable non-behavioral marker of PTSD. This can explain the necessity of bridging conventional approaches to novel technologies in order to create a framework for further discoveries in the treatment of PTSD.